Effects of rheological behaviour on crossflow microfiltration of concentrated shear-thinning dispersions - Mikulášek, Petr (Univerzita Pardubice, 1999)
The effect of process variables on permeate flux during the crossflow microfiltration of concentrated titania dispersions has been investigated. Filtration experiments carried out on ceramic, tubular crossflow modules have shown that increases in transmembrane pressure, crossflow velocity and the degree of dispersion flocculation all result in an improved permeate flux. Rheological work has shown that the titania dispersions exhibit shear-thinning behaviour, conforming to the Herschel-Bulkley or the Casson type models in the shear rate range investigated. Extreme sensitivity with pH was observed, whereby the dispersion viscosity can be changed by as much as an order of magnitude with pH variation at constant volume fraction. The effects of both shear rate and pH are enhanced as the dispersion concentration is increased and the iso-electric point approached. These observations have important implications in crossflow microfiltration of these dispersions.
Keywords: mikrofiltrace; reologické vlastnosti; disperze